Avaliação molecular de genes da família das glutationas S transferases em pacientes com câncer colorretal esporádico - Fleming, Gabriela Helena Rodrigues (2018)
Colorectal cancer is a multifactorial disease, influenced by genetic factors such as genetic polymorphisms and environmental factors such as smoking and drinking habits. Polymorphisms in Phase II genes such as those in the Glutathione S transferase family involved in the metabolism of elimination of carcinogenic substances may contribute to the development of sporadic colorectal cancer. Objectives: To evaluate the association of risk of sociodemographic factors, GSTP1 Ile105Val polymorphism, and GSTT1 and GSTM1 null genotypes with development of sporadic colorectal cancer (SCRC); to investigate the interaction among these polymorphisms with tobacco and alcohol consumption; to verify the association among these polymorphisms and clinical and histopathological parameters of SCRC and to evaluate the influence of the polymorphisms on overall survival time of SCRC patients. Material and Method: A case-control study was conducted including 970 individuals from Brazilian population (232 patients with SCRC and 738 controls). PCR Multiplex and PCR-RFLP techniques were performed for genotyping of the polymorphisms. Results: Age equal or over 62 years (OR = 8.79; (95% CI = 5.90-13.09, p <0.01) and female gender (OR = 2.91, 95% CI = 1.74-4.37, p <0.01) were associated with increased risk for SCRC. The analysis of the polymorphisms revealed association between the GSTM1 polymorphisms and risk for SCRC (OR = 1.45; 95% CI = 1.06-2.00; p=0.02), and between GSTT1 and reduced risk for the disease (OR = 0.65; 95% CI =0.43-0.98; p=0.04). An interaction between the presence of the wild-type allele of GSTP1 Ile105Val polymorphism and the tobacco consumption on risk for SCRC (OR = 2.33; 95% CI = 1.34-4.05; p=0.05) was observed. There was an association between the GSTM1 null genotype and the presence of advanced tumors (OR = 2.33, 95% CI = 1.23-4.41, p = 0.009), and increased risk of SCRC in the presence of combination of non-null GSTT1 / null GSTM1 genotypes (OR = 1.50; 95% CI = 1.03-2.19; p = 0.03) and non-null GSTT1 / GSTM1 null / GSTP1 Val * (OR = 1.85; 95% CI = 1.01-3.36, p = 0.04). Combined genotypes non-null GSTT1 / null GSTM1 (OR = 2.40, 95% CI = 1.19-4.85, p = 0.01) and non-null GSTT1 / null GSTM1 / GSTP1 Val * (OR = 2.92; 95% CI = 1.05-8.12, p = 0.04) were associated with tumor progression. Polymorphisms were not associated with the survival of patients with SCRC. Conclusion: The results of the present study demonstrate that individuals aged 62 years or older and the female gender are more susceptible to SCRC. Polymorphisms of null genotypes GSTT1 and GSTM1 modulate the susceptibility to SCRC in the population studied.